International code of phylogenetic nomenclature (PhyloCode) - Cantino, Philip D.; De Queiroz, Kevin (CRC Press, Taylor & Francis Group, 2020)
"This book will govern the names of clades, while species names will still be governed by traditional codes. PhyloCode is designed so that it can be used concurrently with the rankbased codes. It is not meant not to replace existing systems but to provide an alternative system for governing the application of both existing and newly proposed names"--